ASEAN Charter: A New Beginning for Southeast Asian Nations - Oratmangun, Djauhari (Indonesian Journal of International Law, 2009)
The ASEAN leaders have signed ASEAN Charter in December 2007. A year later, this Charter was ratified by all ASEAN member states thus it become to be entry into force on 15 December 2008. ASEAN Charter reflects the internal momentum and the development of relations between ASEAN and the world. In addition, it also characterizes the common ideals shared by the ASEAN member states. This article will emphasize three subjects. Firtsly, it will examine the factors that push ASEAN member states to move toward ASEAN Charter. Secondly, it will underline the process of drafting int the ASEAN Charter. Thirdly, it will briefly discuss relevant issues which are arisen by the ASEAN Charter.